2013
DOI: 10.1016/j.metabol.2012.08.010
|View full text |Cite
|
Sign up to set email alerts
|

iNOS inhibitor, L-NIL, reverses burn-induced glycogen synthase kinase-3β activation in skeletal muscle of rats

Abstract: Objectives Recent studies suggest that activation of glycogen synthase kinase (GSK)-3β may be involved in burn injury-induced metabolic derangements and protein breakdown in skeletal muscle. However, the mechanism for GSK-3β activation after burn injury is unknown. To investigate the role of inducible nitric oxide synthase (iNOS) in this scenario, a major mediator of inflammation, we examined the effects of a specific inhibitor for iNOS, L-NIL, on GSK-3β activity in skeletal muscle of burned rats. Materials/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…Next, we examined the effects of FTI-277 on burn-induced metabolic alterations. Consistent with previous studies [ 41 ], glycogen content in skeletal muscle of vehicle-treated burned mice was markedly decreased to 22% of that of vehicle-treated sham-burned mice (p<0.05). FTI-277 treatment restored glycogen content in burned mice to the level comparable to those in sham-burned mice ( Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Next, we examined the effects of FTI-277 on burn-induced metabolic alterations. Consistent with previous studies [ 41 ], glycogen content in skeletal muscle of vehicle-treated burned mice was markedly decreased to 22% of that of vehicle-treated sham-burned mice (p<0.05). FTI-277 treatment restored glycogen content in burned mice to the level comparable to those in sham-burned mice ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with our previous studies in rodents [ 31 , 32 , 41 , 47 ], burn injury resulted in: (1) attenuated insulin-stimulated phosphorylation of IR, IRS-1, Akt and GSK-3β (Figs. 2 , 3 ); (2) decreased IRS-1 protein expression ( Fig.…”
Section: Discussionsupporting
confidence: 91%
“…In a second set of experiment, molecular signals of inflammatory and proteolytic pathways were examined at post burn day1 (PBD1). Our previous work documented that proteolytic and inflammatory signals begin to change significantly at day1 and peak at day 2 after burn (31). Meanwhile, our preliminary study also indicated that atrogenes expression were significantly elevated at PBD1 and returned to basal levels at post burn day 3 (PBD3, Supplemental Figure 1).…”
Section: Methodsmentioning
confidence: 98%
“…Nitrotyrosine, a biomarker of inflammation [90][91][92], can increase with iNOS expression in full-thickness third-degree burn injury (40% TBSA burn) [93]. On the other hand, the nitrotyrosine contents are markedly reduced by the iNOS inhibitor [93]. Interestingly, we found one study that shows nitrotyrosine levels was peak in ileum tissue of post-burn rats, whereas this marker was apparent significantly decreased in MT treated rats [78].…”
Section: Effect Of Mt On Other Inflammatory Markersmentioning
confidence: 75%
“…However, recent evidence suggests that intestinal inflammation may contribute to intestinal barrier disruption [88,89]. Nitrotyrosine, a biomarker of inflammation [90][91][92], can increase with iNOS expression in full-thickness third-degree burn injury (40% TBSA burn) [93]. On the other hand, the nitrotyrosine contents are markedly reduced by the iNOS inhibitor [93].…”
Section: Effect Of Mt On Other Inflammatory Markersmentioning
confidence: 99%